Biomedical information technology - Feng, David Dagan (Academic Press series in biomedical engineering., 2008)
The enormous growth in the field of biotechnology necessitates the utilization of information technology for the management, flow and organization of data. The field continues to evolve with the development of new applications to fit the needs of the biomedicine. From molecular imaging to healthcare knowledge management, the storage, access and analysis of data contributes significantly to biomedical research and practice. All biomedical professionals can benefit from a greater understanding of how data can be efficiently managed and utilized through data compression, modelling, processing, registration, visualization, communication, and large-scale biological computing. In addition the book contains practical integrated clinical applications for disease detection, diagnosis, surgery, therapy, and biomedical knowledge discovery, including the latest advances in the field, such as ubiquitous M-Health systems and molecular imaging applications. *The world's most recognized authorities give their "best practices" ready for implementation *Provides professionals with the most up to date and mission critical tools to evaluate the latest advances in the field and current integrated clinical applications *Gives new staff the technological fundamentals and updates experienced professionals with the latest practical integrated clinical applications